Polymer Nanoparticles: Synthesis and Applications - Perumal, Suguna (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint summarizes the ongoing research on the topic of polymer nanoparticles for different applications. It includes functionalization of graphene, silver, and titanium surface with polymers as electrochemical sensors, and antimicrobial agents. The Special Issue "Polymer nanoparticles: Synthesis and Applications" reviews the latest research in polymeric and functionalized nanoparticles, providing a new platform for development and further research. The reprint helps the researcher to fabricate polymeric nanoparticles and nanocomposites with detailed properties.